A Model of Development Mitigation Disaster Based on Digital Eco-Tourism as a Prevention Effort of Forest and Land Fire Disaster Management - Amir Syamsuadi; Diki Arisandi; Liza Trisnawati; Seri Hartati; Luluk Elvitaria; Ardian Adi Putra (Journal of International Conference Proceedings (JICP), 2022)
In 2020, one of the regencies in Riau, Siak, was the second-largest forest and land fire disaster area, which occurred by acute intercourse inspection (ISPA) patients, and reached 4321 suspected. The subject of this research was in Dayun District, Siak Regency, as a pioneering area to develop ecotourism based on disaster mitigation. The disaster mitigation system is an effort to minimize the impact caused by disasters caused by forest and land fires. Effective disaster mitigation has three main elements, namely hazard assessment, warning, and preparation. Ecotourism is a specific tourism activity that deliberates the environmental area and complies with the balance and preservation of nature principles. Ecotourism-based disaster mitigation efforts using the Penta helix model approach, namely strengthening synergy and collaboration of various related parties. The research was descriptive and qualitative by collecting the interview data by data triangulation techniques in describing the information authenticity. The results of this work showed that ecotourism-based disaster mitigation is conducted by utilizing a large and artificial pond called “embung”, as a rainwater reservoir, and also a natural public tourism facility. The government issues this policy by cooperating with Universities and companies through Corporate social responsibility (CSR) programs. Keywords: Disaster, Ecotourism, Mitigation, Forest, Synergy